Control and signal processing applications for mobile and aerial robotic systems - Sergiyenko, Oleg, 1969-; Rivas-Lopez, Moises, 1960-; Flores-Fuentes, Wendy, 1978-; Rodríguez-Quiñonez, Julio C., 1985-; Lindner, Lars (Advances in computational intelligence and robotics (ACIR) book series., 2020)
"This book examines the control and signal processing methods and applications in mobile and aerial robotic systems"--